ANALISIS SEKUNDER KEJADIAN PRE EKLAMPSIA DAN FAKTOR YANG MEMPENGARUHINYA DI RSUD H.BOEJASIN - nooryuliawati, asma; Budi, Setia (Midwifery And Complementary Care, 2024)
Background: Pre-eclampsia is one of the causes of maternal death in Indonesia. Obesity in pregnancy is a sign of a risk factor for pre-eclampsia. At H.Boejasin Hospital, there were maternal deaths due to pre-eclampsia. There are several predisposing factors that cause Pre-Eclampsia, including age, parity, education and others. Objective:. To Knowing the factors that can cause pre-eclampsia at H. Boejasin Hospital. Methods: Using a purposive sampling technique, with a minimum sample of 30 respondents, divided into 2 groups, namely the case and control groups, each consisting of 15 respondents.Results: In pregnancies with PE, obesity is caused by metabolic disorders in the body, high Hb levels are caused by endothelial dysfunction, and the presence of protein in the urine is due to inflammation of the glomeruli which causes glomerular filter function to be disrupted. A pregnant woman can be said to have pre-eclampsia if hypertension is found. cerebral disturbances and epigastric pain even in the absence of protein in the urine.Result: In pregnancies with PE, obesity is caused by metabolic disorders in the body, high Hb levels are caused by endothelial dysfunction, and the presence of protein in the urine is due to inflammation of the glomeruli which causes glomerular filter function to be disrupted. A pregnant woman can be said to have pre-eclampsia if hypertension is found. cerebral disturbances and epigastric pain even in the absence of protein in the urine.Conclusion: Body Weight and Urine Protein have an effect on the p value <0.005, while Hb levels have no effect on the incidence of pre-eclampsia.Keywords: Pregnant Women, Causal Factors, Pre Eclampsia.